2022
DOI: 10.1609/aaai.v36i10.21300
|View full text |Cite
|
Sign up to set email alerts
|

Nice Perfume. How Long Did You Marinate in It? Multimodal Sarcasm Explanation

Abstract: Sarcasm is a pervading linguistic phenomenon and highly challenging to explain due to its subjectivity, lack of context and deeply-felt opinion. In the multimodal setup, sarcasm is conveyed through the incongruity between the text and visual entities. Although recent approaches deal with sarcasm as a classification problem, it is unclear why an online post is identified as sarcastic. Without proper explanation, end users may not be able to perceive the underlying sense of irony. In this paper, we propose a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Specifically, we instructed annotators to revise the textual content of the original sample with minimal changes to reverse its label. In addition, to enhance the revising process of the original sarcastic samples, we provided annotators with the explanation of why the sample is sarcastic, which is supplied by the prior work (Desai, Chakraborty, and Akhtar 2022), to facilitate a deeper sarcasm semantics comprehension. Regarding the original non-sarcastic samples, we found that the samples with stronger emotional tendencies are more easily transformed into sarcastic variants.…”
Section: Experiments Experimental Settingsmentioning
confidence: 99%
“…Specifically, we instructed annotators to revise the textual content of the original sample with minimal changes to reverse its label. In addition, to enhance the revising process of the original sarcastic samples, we provided annotators with the explanation of why the sample is sarcastic, which is supplied by the prior work (Desai, Chakraborty, and Akhtar 2022), to facilitate a deeper sarcasm semantics comprehension. Regarding the original non-sarcastic samples, we found that the samples with stronger emotional tendencies are more easily transformed into sarcastic variants.…”
Section: Experiments Experimental Settingsmentioning
confidence: 99%
“…Delving further, Kumar et al (2022) delve into dissecting the discourse structure within sarcastic conversations and introduce the Sarcasm Explanation in Dialogue (SED) task. In a similar vein, Desai, Chakraborty, and Akhtar (2022) bring to the fore an innovative challenge named Multimodal Sarcasm Explanation (MuSE), revolving around generating a natural language explanation for a multimodal sarcastic expression encompassing both an image and a caption.…”
Section: Related Workmentioning
confidence: 99%
“…In (Desai, Chakraborty, and Akhtar 2022), the authors introduce a new task known as Multimodal Sarcasm Explanation (MuSE). In this problem, the objective is to provide a natural language explanation for a multimodal sarcastic post, which comprises both an image and a caption.…”
Section: Related Workmentioning
confidence: 99%
“…However, figurative meaning is also prevalent in visual phenomena, such as visual metaphors (Akula et al, 2023;Chakrabarty et al, 2023), multimodal sarcasm (Desai et al, 2022), and humor (Hessel et al, 2023;Hwang and Shwartz, 2023). Yet so far most of the work on vision and language models (VLMs) has focused on understanding literal meaning in images and captions (e.g., ScienceQA , MMMU (Yue et al, 2024)) including work on explainable visual entailment (Kayser et al, 2021).…”
Section: Image (Premise)mentioning
confidence: 99%